2016
DOI: 10.5424/sjar/2016142-8230
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Consumer’s willingness to pay for indigenous meat products: The case of a Spanish sheep breed

Abstract: European farmers of indigenous local breeds have benefited from European Union economic support in the past and it is forecast to continue being supported in the future. However, it is in the public debate that economic support cannot last forever. Then, for the long-run maintenance of indigenous local breeds to be possible, the derived meat products from these breeds should be demanded by consumers or at least by a group of local consumers. This is the aim of this paper, to study consumers’ demand for indigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Most incentive-compatible studies were conducted in the United States (Yue and Tong 2009;Costanigro et al 2011;Adalja et al 2015;Kecinski et al 2017;Fan et al 2019;Li et al 2020a;2020b;Wu et al 2015) or Europe (Gracia et al 2012;de-Magistris and Gracia 2016;Wägeli et al 2016;Bazzani et al 2017;Sanjuán-López and Resano-Ezcaray 2020) and rarely in other parts of the world like South America (Kallas et al 2019). In many cases, the incentive-compatible research has also found that consumers are willing to pay a premium for local foods including fresh produce and nuts (Yue and Tong 2009;Costanigro et al 2011;Grebitus et al 2013;de-Magistris and Gracia 2016;Fan et al 2019;Sanjuán-López and Resano-Ezcaray 2020;Moreno and Malone 2021), processed foods such as applesauce (Bazzani et al 2017) and wine (Grebitus et al 2013), and animal products (Gracia et al 2012;Adalja et al 2015;Gracia and de-Magistris 2016;Wägeli et al 2016;Kallas et al 2019;Li et al 2020a;2020b). However, other studies have found that only small segments of consumers are willing to pay more (Adalja et al 2015;de-Magistris and Gracia 2016;Li et al 2020a).…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Most incentive-compatible studies were conducted in the United States (Yue and Tong 2009;Costanigro et al 2011;Adalja et al 2015;Kecinski et al 2017;Fan et al 2019;Li et al 2020a;2020b;Wu et al 2015) or Europe (Gracia et al 2012;de-Magistris and Gracia 2016;Wägeli et al 2016;Bazzani et al 2017;Sanjuán-López and Resano-Ezcaray 2020) and rarely in other parts of the world like South America (Kallas et al 2019). In many cases, the incentive-compatible research has also found that consumers are willing to pay a premium for local foods including fresh produce and nuts (Yue and Tong 2009;Costanigro et al 2011;Grebitus et al 2013;de-Magistris and Gracia 2016;Fan et al 2019;Sanjuán-López and Resano-Ezcaray 2020;Moreno and Malone 2021), processed foods such as applesauce (Bazzani et al 2017) and wine (Grebitus et al 2013), and animal products (Gracia et al 2012;Adalja et al 2015;Gracia and de-Magistris 2016;Wägeli et al 2016;Kallas et al 2019;Li et al 2020a;2020b). However, other studies have found that only small segments of consumers are willing to pay more (Adalja et al 2015;de-Magistris and Gracia 2016;Li et al 2020a).…”
Section: Related Literaturementioning
confidence: 99%
“…In many cases, the incentive-compatible research has also found that consumers are willing to pay a premium for local foods including fresh produce and nuts (Yue and Tong 2009;Costanigro et al 2011;Grebitus et al 2013;de-Magistris and Gracia 2016;Fan et al 2019;Sanjuán-López and Resano-Ezcaray 2020;Moreno and Malone 2021), processed foods such as applesauce (Bazzani et al 2017) and wine (Grebitus et al 2013), and animal products (Gracia et al 2012;Adalja et al 2015;Gracia and de-Magistris 2016;Wägeli et al 2016;Kallas et al 2019;Li et al 2020a;2020b). However, other studies have found that only small segments of consumers are willing to pay more (Adalja et al 2015;de-Magistris and Gracia 2016;Li et al 2020a).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Food originated from indigenous breeds of sheep is an option to access and develop alternative markets [ 14 16 ]. However, information about locally adapted sheep in South America is rather poor, which includes breeds such as Crioula Lanada [ 17 ] and Pantaneiro sheep [ 18 ].…”
Section: Introductionmentioning
confidence: 99%